Low scores, high standards- a case study on Coop’s sustainability declaration - Malthed, Caroline; Wrenfelt, Tuva (SLU/Dept. of Forest Economics, 2022)
The earth's ecosystems are changing due to human activities, and it is urgent that we transform our way of living to avoid further negative effects on climate change. Food production has the single biggest impact on global environmental changes, since 21-37% of the world's total greenhouse gas emissions comes from the agricultural systems. Sweden is highly dependent on imports for its food supply which makes it sensitive for external pressures and global events. Retail chains are today the established main source for purchasing foodstuffs. These actors are therefore in a position where they can create barriers for food producers to enter the market. This project is a commission from the Swedish retail chain Coop Sweden (Coop) which also constituted the case study. They aspire to transform the food industry by implementing their sustainability declaration as a new supplier standard. The reason for this is that they wish to broaden their assortment of sustainable food products that can be offered to consumers. The aim for this study was to identify how Coop´s supplier standard could be implemented for small-scale producers, to create sustainable and resilient food systems. Semi-structured interviews were conducted with purchasers and small-scale producers from Coop´s consumer unions Norrbotten, Värmland and Gotland. Their answers were analysed using theories and concepts of Institutional theory, CSR, standards, Channel theory and gatekeepers. This study´s results show that the interviewees share an overall understanding of the definition of local food as: food that has been produced within a defined geographical region. It is also evident from the results that to successfully implement the sustainability declaration, it needs to lead to increased income for the small-scale producers. The results further show that all the interviewees are willing to work to continuously improve their sustainability work but that they need support from Coop in the process. This could be done by offering education, clear guidelines, and long supplier agreements. A standardised and shared industry system for reporting key figures regarding sustainability impact is also requested by the interviewed producers. All interviewees mentioned that they are concerned over the consequences that may come from the current war in Ukraine. The timing of higher supplier requirements may therefore be ill suited due to ongoing global events. However, the climate change and environmental changes are urgent, which require a systematic change in our way of living. It is therefore of utmost importance to motivate small-scale producers to reduce their sustainability impact, so that all food systems can become more sustainable.